A new calcium 2,5-dihydroxybenzoate: Synthesis, characterization and antioxidant studies and stress mediated cytotoxity in MCF-7 cells - Monika Kalinowska; Liliana Mazur; Agata Jabłońska-Trypuć; Włodzimierz Lewandowski (Journal of Saudi Chemical Society)
The structure and composition of the calcium 2,5-dihydroxybenzoate (calcium gentisate) were studied by single-crystal and powder X-ray diffraction. Single-crystal X-ray analysis revealed that the compound crystallizes in the orthorhombic space group Pbcn. The Ca(II) cation is coordinated in a monodentate fashion by two symmetry-related gentisate anions and five water molecules. The metal ion and one of the water molecules are located on a 2-fold rotation axis. The adjacent monomeric units are assembled into a 3-D supramolecular framework via O–H…O hydrogen bonds. Comparison of the experimental powder pattern with that simulated from single-crystal X-ray data confirmed the purity and homogeneity of the sample. The FT-IR, UV/VIS, 1H and 13C NMR spectra of the calcium 2,5-dihydroxybenzoic acid were registered and analysed. Moreover the effect of calcium complex and 2,5-dihydroxybenzoic acid on basic oxidative stress parameters, such as thiol group content and lipid peroxidation in the human breast cancer cells MCF-7 was studied. The antiradical and ferric reducing power of these compounds was measured by DPPH, CUPRAC and FRAP methods. The chemical reactivity parameters (e.g. HOMO and LUMO orbitals, ionization potential, electron affinity) for Ca 2,5-dHB and 2,5-dHB were calculated at B3LYP/6-311++G∗∗ level of theory and discussed in relation to their antioxidant properties. Keywords: 2,5-Dihydroxybenzoic acid, Gentisic acid, 2,5-Dihydroxybenzoate, Calcium, Pro-/antioxidant, MCF-7